2021
DOI: 10.1051/smdo/2021021
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of elevator wire ropes

Abstract: In this research paper design and analysis of wire ropes used in elevator have been presented. The main objective of this study is to find the best practices on handling wire ropes for safety and to reduce the downtime of elevators due to wire rope failures. Design calculations have been done to calculate the apt dimensions and design is constructed on Auto Desk inventor software and the analysis have been performed using Ansys. Two configurations of the wire ropes have been studied and from this result it can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…To determine the failure criteria of wire rope, there are recommendations to conduct a yearly magnetic test. Other researchers [4] who have inspected the wire ropes commonly used in the gas, oil, and mining industries concluded that electromagnetic nondestructive methods have potential and could be helpful to develop the failure and discard criteria [5]. In [6],…”
Section: Magnetic Methods To Diagnose Steel Wire Rope Damagementioning
confidence: 99%
“…To determine the failure criteria of wire rope, there are recommendations to conduct a yearly magnetic test. Other researchers [4] who have inspected the wire ropes commonly used in the gas, oil, and mining industries concluded that electromagnetic nondestructive methods have potential and could be helpful to develop the failure and discard criteria [5]. In [6],…”
Section: Magnetic Methods To Diagnose Steel Wire Rope Damagementioning
confidence: 99%